Agronomic evaluation of Stylosanthes capitata accessions - Botrel, Milton de Andrade; Alvim, Maurílio José; Xavier, Deise Ferreira; Salvati, José Augusto (Pesquisa Agropecuaria Brasileira, 1991)
The agronomic evaluation of twenty-five accessions of S. capitata was conducted in small plots at the Dairy Cattle Research Center, (EMBRAPA/CNPGL), in a hilly area with low fertility soil. The characteristics evaluated included growth rates during the dry season and during the rainy season, resistance to disease and insect damage, seed production and concentration of N, P, Ca and Mg in the tops. Dry matter (DM) production, disease resistance and seed production were different among accessions. Monthly growth rates during the rainy seasons changed from 135 g of DM/m2 for the accession BRA 002887, up to 237 g of DM/m2 for BRA 007919; during the dry season the values were for the accession BRA 002887 up to 33 for BRA 008401. Seed production varied from 20 g/m2 for the accession BRA 008583 up to 69 for BRA 009059. About 28% of the accessions were disease resistants and 36% insect tolerant. There was no difference among the accessions concerning mineral contents in the tops. The most promising accessions were: BRA 008401, BRA 008357, BRA 008966, BRA 008562 and BRA 009059.